THE CONVERGENCE OF LEGISLATION ON CYBERCRIME AND DATA PROTECTION IN SOUTH AFRICA: A Practical Approach to the Cybercrimes Act 19 of 2020 and the Protection of Personal Information Act 4 of 2013 - Sizwe Snail ka Mtuze (Obiter, 2022)
This article seeks to give a historical background to the development of cybercrime laws in South Africa. It commences with a discussion on the common-law position regarding cyber-criminality then the article goes on to discuss the Electronic Communications Transactions Act (ECT) and the new Cybercrimes Act. This is followed by a discussion on Protection of Personal Information Act (POPIA) and same converges with the Cybercrimes Act, as well as the POPIA.